2014
DOI: 10.1103/physrevlett.112.037001
|View full text |Cite
|
Sign up to set email alerts
|

Selective Equal-Spin Andreev Reflections Induced by Majorana Fermions

Abstract: In this work, we find that Majorana fermions induce selective equal spin Andreev reflections (SESARs), in which incoming electrons with certain spin polarization in the lead are reflected as counter-propagating holes with the same spin. The spin polarization direction of the electrons of this Andreev reflected channel is selected by the Majorana fermions. Moreover, electrons with opposite spin polarization are always reflected as electrons with unchanged spin. As a result, the charge current in the lead is spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
128
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 43 publications
4
128
1
Order By: Relevance
“…This process was first proposed in a semiconductor wire/SC structure in which MZMs exist at two ends of the wire. 43 The proposed SSAR of the MZM in 1D wire can be generalized to a 2D TSC. In the latter case, the spin of the MZM in the vortex core has a spatial distribution and is not conserved.…”
Section: Experimental Detection Of Mzmmentioning
confidence: 99%
See 1 more Smart Citation
“…This process was first proposed in a semiconductor wire/SC structure in which MZMs exist at two ends of the wire. 43 The proposed SSAR of the MZM in 1D wire can be generalized to a 2D TSC. In the latter case, the spin of the MZM in the vortex core has a spatial distribution and is not conserved.…”
Section: Experimental Detection Of Mzmmentioning
confidence: 99%
“…Therefore, the Andreev reflection at the vortex center is expected to be spin-selective. [42][43][44] Via an spin-polarized STM, 45,46 we can inject spin-polarized tunneling current in STS measurements and observe the zero bias conductance change caused by the SSAR from the MZM when flipping the spin of the tunneling electrons. 47,48 It is worth noting that only a small magnetic field is sufficient to excite vortices on the TI surface and hence the spin-polarized MZM in the vortex core.…”
Section: Experimental Detection Of Mzmmentioning
confidence: 99%
“…(2) We assume that spin-down sector only of the dot is coupled to the MS due to its helical properties [9]. ε m ∼ e −L/ξ represents the coupling between two Majorana states, where L is the wire length and ξ is the superconducting coherence length.…”
Section: Gmentioning
confidence: 99%
“…This introduces great difficulty in detection of the MZM by using normal STM=STS with a nonpolarized tip. He et al have recently proposed a novel property of MZM in a 1D system [16], where the Andreev reflection (AR) is spin selective. They showed that MZM induces selective equal spin AR, in which incoming electrons with certain spin polarization in the lead are reflected as counterpropagating holes with the same spin [7].…”
mentioning
confidence: 99%
“…3(a). Therefore, the AR at r ¼ 0 is expected to be spin selective, and can be probed in spin polarized (SP) STM=STS [16][17][18].…”
mentioning
confidence: 99%